The Influence of Technological Development on Language Practices in the Digital Age on Apps X - Fajrin, Cahyani; Sulthan, Faqih (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
In today's era of globalization, technological developments are becoming increasingly rapid, and significant transformations are occurring in various aspects. These technological changes have transformed the way people communicate and practice language with digital apps. These changes become a platform to influence, maintain, and develop language for interaction. This research aims to find out the significant contribution of technology that affects language practice in the digital era, making more creative communication and innovative in X apps. It will also examine the impact, effectiveness, and potential benefits of integrated communication from language and technology. The research method is a descriptive qualitative method that uses data collected based on words and images, and in this study, data analysis is used as a discussion technique. Content analysis is a systematic examination of data sources. The results of this study provide valuable insights into how humans adapt to technology in language practices to communicate creatively, highlighting code-mixing and the use of new terms as elements that shape the communication landscape in today's digital age.